Application of the EFA to Measure the Relationship between Engagement,Organizational Climate and Work Performance in Workers of High School Education Subsystems - Alamilla López, Norma Edith (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJECTIVE: To identify underlying structures between the constructs: Engagement, Organizational Climate and Work Performance in workers of High School Education Institutions (HSEI) in the State of Tabasco, through an Exploratory Factor Analysis (EFA).MATERIAL AND METHOD: A statistical analysis was carried out with a quantitative deductive approach, with a non-experimental cross-sectional design. The sample consisted of 125 workers from nine subsystems in Tabasco. The EFA was applied, using the maximum likelihood extraction method and the varimax rotation with Kaiser normalization.RESULTS: The 16 identified factors explained 62.46% of the total variance of the data. The adjustment capacity of the model was significant (p = 0.018), this strengthens the validity of the factor analysis. The results indicate that the questionnaire satisfactorily measures three dimensions: Engagement, Organizational Climate and Work Performance, identifying an underlying structure close to the theoretical model.CONCLUSIONS: The questionnaire successfully showed the dimensions and, in the database close to the theoretical model an underlying structure was identified.   In addition, the existing relationship between organizational and work factors was identified, highlighting its importance for the proper functioning of the High School Education Institutions (HSEI).
Keywords: Working conditions; Quality of service; Exploratory Factor Analysis (EFA).